Standard of proof in Europe - Tichý, Luboš (Veröffentlichungen zum Verfahrensrecht, 2019)
Das vorliegende Buch gibt einen Überblick, wie die maßgeblichen europäischen Rechtsordnungen einem der Kernprobleme des Zivilprozessrechts gegenübertreten: dem Beweismaß. Vierzehn herausragende Rechtswissenschaftler erörtern die Herangehensweise ihres Rechtssystems und tragen so zur Suche nach einem allgemeingültigen Standard bei.InhaltsübersichtPavel Holländer: Proof, theory of truthfulness and the purposes of procedure – Mark Schweizer: The standard of proof as a decision threshold – Christoph Kern: Probability as an element of the standard of proof – Magne Strandberg: The more probable than not standard – a critical approach – Christoph Althammer/Madeleine Tolani: Proof of causation in German tort law – Hans Jürgen Ahrens: The standard of proof – the German approach – Walter Rechberger: The Austrian approach and the inherent connection between the standard of proof and the burden of proof – Michael Stürner: Evaluation of evidence and the standard of proof in the ELI/UNIDROIT European Rules of Civil Procedure – Jan Balarin: The Czech approach – Emmanuel Jeuland: The standard of proof and the French approach – Roberto Poli: The Italian concept of the standard of proof – John Sorabji: The English approach to the standard of proof – Luboš Tichý: Main problems from the perspective of a comparative analysis